The Effect of the Regulatory Focus Organizational Culture on the Innovative Work Behavior: The Mediating Effect of the Positive and Negative Feedback Seeking Behavior - Heo, ChangGoo; Kwon, Eun-a; Hyun, Kwang-eun (Korean Journal of Industrial and Organizational Psychology, 2021)
The aims of this study were to identify the effects of regulatory focus organizational culture and feedback seeking behavior on innovative work behavior and to confirm the mediating effect of feedback seeking behavior. For this purpose, an online survey was conducted on employees of domestic companies and a total of 245 data were analyzed. The main results of this study are as follows. First, in the relationship between organizational culture and innovative work behavior, the promotion focus organizational culture increased innovative work behavior, but the prevention focus organizational culture did not affect innovative work behavior. Second, in the relationship between organizational culture and feedback seeking behavior, the promotion focus organizational culture increased both positive and negative feedback seeking behavior, but the prevention focus organizational culture increased only positive feedback seeking behavior. Third, in the relationship between feedback seeking behavior and innovative work behavior, negative feedback seeking behavior had a positive effect on innovative work behavior, but positive feedback seeking behavior did not affect innovative work behavior. Fourth, the promotion focus organizational culture had indirect effects on innovative work behavior through negative feedback seeking behavior. The results of this study suggest that the more companies that pursue innovation, the more they need to form a promotion focus organizational culture, so that employees can actively accept and utilize negative feedback without being wary of negative feedback.